Microstructural and plasmonic modifications in Ag–TiO2 and Au–TiO2 nanocomposites through ion beam irradiation - Chakravadhanula, Venkata Sai Kiran; Mishra, Yogendra Kumar; Kotnur, Venkata Girish; Avasthi, Devesh Kumar; Strunskus, Thomas; Zaporotchenko, Vladimir; Fink, Dietmar; Kienle, Lorenz; Faupel, Franz (Beilstein Journal of Nanotechnology, 2014)
The development of new fabrication techniques of plasmonic nanocomposites with specific properties is an ongoing issue in the plasmonic and nanophotonics community. In this paper we report detailed investigations on the modifications of the microstructural and plasmonic properties of metal–titania nanocomposite films induced by swift heavy ions. Au–TiO2 and Ag–TiO2 nanocomposite thin films with varying metal volume fractions were deposited by co-sputtering and were subsequently irradiated by 100 MeV Ag8+ ions at various ion fluences. The morphology of these nanocomposite thin films before and after ion beam irradiation has been investigated in detail by transmission electron microscopy studies, which showed interesting changes in the titania matrix. Additionally, interesting modifications in the plasmonic absorption behavior for both Au–TiO2 and Ag–TiO2 nanocomposites were observed, which have been discussed in terms of ion beam induced growth of nanoparticles and structural modifications in the titania matrix.
Keywords: noble metal–titania nanocomposite; surface plasmon resonance; swift heavy ions

(untitled) - Jain, P. K.; Huang, X.; El-Sayed, I. H.; El-Sayed, M. A. (Acc. Chem. Res., 2008)

(untitled) - Jamali, M.; Hedayati, M. K.; Mozooni, B.; Javaherirahim, M.; Abdelaziz, R.; Zillohu, A. U.; Elbahri, M. (Adv. Mater., 2011)

(untitled) - Atwater, H. A.; Polman, A. (Nat. Mater., 2010)

(untitled) - Elbahri, M.; Hedayati, M. K.; Chakravadhanula, V. S. K.; Jamali, M.; Strunskus, T.; Zaporojtchenko, V.; Faupel, F. (Adv. Mater., 2011)

Optical properties of metal clusters - Kreibig, U.; Vollmer, M. (Springer, 1995)

Optical Properties of Nanoparticle Systems - Quinten, M. (Wiley-VCH, 2011)

(untitled) - Caseri, W. (Macromol. Rapid Commun., 2000)

(untitled) - Mohapatra, S.; Mishra, Y. K.; Avasthi, D. K.; Kabiraj, D.; Ghatak, J.; Varma, S. (J. Phys. D: Appl. Phys., 2007)

(untitled) - Takele, H.; Greve, H.; Pochstein, C.; Zaporojtchenko, V.; Faupel, F. (Nanotechnology, 2006)

(untitled) - Wu, W.; Liao, L.; Zhang, S.; Zhou, J.; Xiao, X.; Ren, F.; Sun, L.; Dai, Z.; Jiang, C. (Nanoscale, 2013)

(untitled) - Mishra, Y. K.; Chakravadhanula, V. S. K.; Hrkac, V.; Jebril, S.; Agarwal, D. C.; Mohapatra, S.; Avasthi, D. K.; Kienle, L.; Adelung, R. (J. Appl. Phys., 2012)

(untitled) - Liu, H.; Ye, F.; Ma, X.; Cao, H.; Yang, J. (CrystEngComm, 2013)

(untitled) - Lu, Q.; Lu, Z.; Lu, Y.; Lv, L.; Ning, Y.; Yu, H.; Hou, Y.; Yin, Y. (Nano Lett., 2013)

(untitled) - Khan, M. M.; Ansari, S.; Amal, M. I.; Lee, J.; Cho, M. H. (Nanoscale, 2013)

(untitled) - Matsubara, K.; Tatsuma, T. (Adv. Mater., 2007)

(untitled) - Chen, X.; Mao, S. S. (Chem. Rev., 2007)

(untitled) - Marjanović, N.; Vujisić, M.; Stanković, K.; Osmokrović, P. (Radiat. Eff. Defects Solids, 2011)

(untitled) - Sanz, R.; Jensen, J.; Johansson, A.; Skupinski, M.; Possnert, G.; Boman, M.; Hernandez-Vélez, M.; Vazquez, M.; Hjort, K. (Nanotechnology, 2007)

(untitled) - Fink, D.; Chadderton, L. T. (Braz. J. Phys., 2005)

(untitled) - Toulemonde, M.; Trautmann, C.; Balanzat, E.; Hjort, K.; Weidinger, A. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2004)

(untitled) - Ridgway, M. C.; Giulian, R.; Sprouster, D. J.; Kluth, P.; Araujo, L. L.; Llewellyn, D. J.; Byrne, P.; Kremer, F.; Fichtner, P. F. P.; Rizza, G.; Amekura, H.; Toulemonde, M. (Phys. Rev. Lett., 2011)

(untitled) - Avasthi, D. K.; Mishra, Y. K.; Singh, F.; Stoquert, J. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)

(untitled) - Mishra, Y. K.; Kabiraj, D.; Avasthi, D. K.; Pivin, J. C. (Radiat. Eff. Defects Solids, 2007)

(untitled) - Mishra, Y. K.; Avasthi, D. K.; Kulriya, P. K.; Singh, F.; Kabiraj, D.; Tripathi, A.; Pivin, J. C.; Bayer, I. S.; Biswas, A. (Appl. Phys. Lett., 2007)

(untitled) - Mishra, Y. K.; Singh, F.; Avasthi, D. K.; Pivin, J. C.; Malinovska, D.; Pippel, E. (Appl. Phys. Lett., 2007)

(untitled) - Toulemonde, M.; Costantini, J.; Dufour, C.; Meftah, A.; Paumier, E.; Studer, F. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1996)

(untitled) - Rizza, G.; Coulon, P. E.; Khomenkov, V.; Dufour, C.; Monnet, I.; Toulemonde, M.; Perruchas, S.; Gacoin, T.; Mailly, D.; Lafosse, X.; Ulysse, C.; Dawi, E. (Phys. Rev. B, 2012)

(untitled) - Dawi, E.; Vredenberg, M.; Rizza, G.; Toulemonde, M. (Nanotechnology, 2011)

(untitled) - Afra, B.; Rodriguez, M. D.; Trautmann, C.; Pakarinen, O. H.; Djurabekova, F.; Nordlund, K.; Bierschenk, T.; Giulian, R.; Ridgway, M. C.; Rizza, G.; Kirby, N.; Toulemonde, M.; et al. (J. Phys.: Condens. Matter, 2013)

(untitled) - Dufour, C.; Khomenkov, V.; Rizza, G.; Toulemonde, M. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Rizza, G.; Attouchi, F.; Coulon, P.-E.; Perruchas, S.; Gacoin, T.; Monnet, I.; Largeau, L. (Nanotechnology, 2011)

(untitled) - Ruffino, F.; De Bastiani, R.; Grimaldi, M. G.; Bongiorno, C.; Giannazzo, F.; Roccaforte, F.; Spinella, C.; Raineri, V. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2007)

(untitled) - Thakurdesai, M.; Mohanty, T.; John, J.; Gundu Rao, T. K.; Raychaudhuri, P.; Bhattacharyya, V.; Kanjilal, D. (J. Nanosci. Nanotechnol., 2008)

(untitled) - Kumar, A.; Jaiswal, M. K.; Kanjilal, D.; Joshi, R. K.; Mohanty, T. (Appl. Phys. Lett., 2011)

(untitled) - Trivedi, S. J.; Khan, S. A.; Joshi, U. S. (Radiat. Eff. Defects Solids, 2013)

(untitled) - Singh, A. P.; Kumari, S.; Tripathi, A.; Singh, F.; Gaskell, K. J.; Shrivastav, R.; Dass, S.; Ehrman, S. H.; Satsangi, V. R. (J. Phys. Chem. C, 2010)

(untitled) - Thakurdesai, M.; Kanjilal, D.; Bhattacharyya, V. (Semicond. Sci. Technol., 2009)

(untitled) - Mishra, Y. K.; Mohapatra, S.; Kabiraj, D.; Mohanta, B.; Lalla, N.; Pivin, J.; Avasthi, D. (Scr. Mater., 2007)

(untitled) - Chakravadhanula, V. S. K.; Hrkac, T.; Zaporojtchenko, V.; Podschun, R.; Kotnur, V. G.; Kulkarni, A.; Strunskus, T.; Kienle, L.; Faupel, F. (J. Nanosci. Nanotechnol., 2011)

(untitled) - Chakravadhanula, V. S. K.; Kübel, C.; Hrkac, T.; Zaporojtchenko, V.; Strunskus, T.; Faupel, F.; Kienle, L. (Nanotechnology, 2012)

(untitled) - Klaumünzer, S. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2004)

(untitled) - Pivin, J. C.; Roger, G.; Garcia, M. A.; Singh, F.; Avasthi, D. K. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2004)

(untitled) - Zribi, M.; Kanzari, M.; Rezig, B. (Thin Solid Films, 2008)

(untitled) - Enyashin, A. N.; Ivanovskii, A. L. (Russ. J. Inorg. Chem., 2006)

(untitled) - Thakurdesai, M.; Kanjilal, D.; Bhattacharyya, V. (Appl. Surf. Sci., 2012)

(untitled) - Rath, H.; Dash, P.; Som, T.; Satyam, P. V.; Singh, U. P.; Kulriya, P. K.; Kanjilal, D.; Avasthi, D. K.; Mishra, N. C. (J. Appl. Phys., 2009)

(untitled) - Kelly, K. L.; Coronado, E.; Zhao, L. L.; Schatz, G. C. (J. Phys. Chem. B, 2003)

(untitled) - Aumayr, F.; Facsko, S.; El-Said, A. S.; Trautmann, C.; Schleberger, M. (J. Phys.: Condens. Matter, 2011)

(untitled) - Bartkowski, S.; Neumann, M.; Kurmaev, E. Z.; Fedorenko, V. V.; Shamin, S. N.; Cherkashenko, V. M.; Nemnonov, S. N.; Winiarski, A.; Rubie, D. C. (Phys. Rev. B, 1997)

(untitled) - Stadelmann, P. (Ultramicroscopy, 1987)

James Ziegler - SRIM & TRIM